ALIH KODE DAN CAMPUR KODE DALAM KEGIATAN DINIYAH DI PONDOK PESANTREN NURUL UMMAH PUTRI KOTAGEDE YOGYAKARTA - Siti Halimatus Sa'diyah; Basuki Basuki (Universitas Sarjanawiyata Tamansiswa, 2019)
The purposes of the research are, (1) describe the form of code-switching in diniyah program PPNUPI, (2) describe the cause of code-switching in diniyah program PPNUPI, (3) describe the form of code mixing in diniyah program PPNUPI, and (4) describe the cause of code mixing in diniyah program PPNUPI. The research is qualitative descriptive research. The data used are the sentence /ustaz’s dialogue/ ustazah and the students that obtain of code switching and code mixing in diniyah program. The source of data is from a language using the mathodes of collecting data are simak bebas libat cakap method, recording method and noting method. The analysis method used is padan translational method, and pragmatic with pilah unsur penentu technique and agih methot with bagi unsur langsung technique . the method the result of the research are 1) The from of code-switching in diniyah program PPNUPI insteads of, (a) code-switching from Indonesia to Javanese, (b) code swiching from Javanese to Indonesia, (c) code-switching from Indonesia of Arabic, (d) code-switching from Arabic to Indonesia, (e) code-switching from Arabic to Javanese, (f) code-switching from Indonesia to English. 2)The couse of code-switching in diniyah program PPNUPI instead of (a) the narrator, (b) the narrated, (c) the third person, and (d) the topic charging. (3) The from of code mixing in diniyah program PPNUPI is divided into to forms, a) inner-code-mixing instead of (i) word infixation, (ii) phrase infixation, (iii) phrase infixation. (4) The cause of code mixing in diniyah program PPNUPI instead of (a) the special characteristic of the region, (b) the fidelity of praying, and (c) the intellectualism.